The Research on How Cloud Computing Impact Primary Education in China - He, Ruilin (2022)
With the rapid development of information technology, cloud computing comes into the world, and it is widely used in the field of education. This article will examine how cloud computing impacts primary education in China. The study conducts semi-structured interviews with teachers in three primary schools in Chongqing, China, to find out what impacts cloud computing has had on China’s primary school students, teachers, and schools. Based on the analysis of these impacts, some suggestions regarding the future application of cloud computing are put forward for these three primary schools.